The role of rhetoric in the politicization of ethnicity - Božić Roberson, Agneza (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2007)
Slobodan Milošević was the first acting Head of State to be charged and tried by an International Tribunal with the commission of serious violations of international humanitarian law, including genocide. He was the Serbian leader and then president of rump Yugoslavia in the 1990s, during the bloodiest wars in post-Second World War Europe, when hundreds of thousands of people were being killed and misplaced by the wars in Croatia, Bosnia and Kosovo. Although Milošević is subject of many analyses because of his political and war crimes, it should not be forgotten that Milošević established himself as a populist Serbian leader through his rhetoric and spoke his way to power. Analysis of Milošević's speeches should help us to understand the power of his rhetoric to influence and shape the events that contributed to the beginning of ethnopolitical conflicts on the Yugoslav territory. The purpose of this paper is twofold. First, it provides a theoretical framework for the analysis of rhetoric within the political arena, with an emphasis on the process of the politicization of ethnicity. Second, in a case study, I examinethree of Milošević's speeches that represent an important part of the larger Kosovo campaign. This study will analyze three of Miloševiććs key speeches. The first public speech of April 24, 1987 in Kosovo Polje, was delivered to the Serbs in Kosovo, the Albanian-populated province of Republic of Serbia. This event marked the public beginning of Milošević's populist leadership strategy. The second is the speech of November 19, 1988, deliv-eredat the Meeting of the Brotherhood and Unity in Belgrade. In this speech Milošević openly invited the Serbs to fight for the establishment of the Serbian state. The third is the speech of June 28, 1989, in Gazimestan, delivered as part of the commemoration of the 600th anniversary of the Battle of Kosovo and Serbia's defeat by the Turks. This speech was the most obvious evocation of the Kosovo myth in celebrating the unity of the Serbs and Milošević's greatest threat to the Yugoslav federation.
Keywords: Milošević, Slobodan, 1941-2006; politična retorika; etnični konflikti; Jugoslavija; Yugoslavia; Serbia; Srbija; Kosovo; politični govori